1990
DOI: 10.1126/science.2294602
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual Deficits and the Activity of the Color-Opponent and Broad-Band Pathways at Isoluminance

Abstract: The deficits in texture, motion, and depth perception incurred in monkeys at isoluminance were compared with the responses of neurons of the color-opponent and broad-band systems in the lateral geniculate nucleus. Texture perception, assumed to be carried by the color-opponent system, and motion and depth perception, ascribed to the broad-band pathway, were all found to be compromised but not abolished at isoluminance. Correspondingly, both the color-opponent and the broad-band systems were affected at isolumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0
2

Year Published

1991
1991
2005
2005

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(71 citation statements)
references
References 19 publications
4
65
0
2
Order By: Relevance
“…These two areas were always simultaneously active, but responses of both areas were about 30 ms delayed for the equiluminant stimuli. This delay may correspond to slower conduction of signals through the wavelength-sensitive parvocellular than the broad-band magnocellular retinocortical pathway (35) or to a weaker retinocortical signal at equiluminance (36). At longer latencies, the cortical dynamics was different for each stimulus.…”
Section: Resultsmentioning
confidence: 99%
“…These two areas were always simultaneously active, but responses of both areas were about 30 ms delayed for the equiluminant stimuli. This delay may correspond to slower conduction of signals through the wavelength-sensitive parvocellular than the broad-band magnocellular retinocortical pathway (35) or to a weaker retinocortical signal at equiluminance (36). At longer latencies, the cortical dynamics was different for each stimulus.…”
Section: Resultsmentioning
confidence: 99%
“…Second, a*b* represents colors along two color-opponent dimensions: a* extends from green to red and b* from blue to yellow. It is generally agreed that the visual system processes color along such oppositions (see Logothetis, Schiller, Charles, & Hurlbert, 1989). The second interesting property of L*a*b* is that it is close to perceptual uniformity.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Both psychophysical and neurophysiological experiments have shown that the motion stream pools information from many orientations that are moving in the same direction to generate precise estimates of a moving object's direction and speed [19][20][21][27][28][29] . Lesions of the form system also show that, on its own, the motion system can make only coarse depth estimates 30,31 . Thus it seems reasonable that the orientationally tuned form system generates emergent representations of forms with precise depth estimates, whereas the directionally tuned motion system -on its own -can generate only coarse depth estimates.…”
Section: Complementary Form and Motion Interactionsmentioning
confidence: 99%